THE IMPORTANCE OF BUDGET TRANSPARENCY IN THE UNION: A STUDY ON THE SIGA BRAZIL PORTAL - Gadelha da Silva Junior, André; Eduardo Leite Costa, Carlos; Gabriel Garcia Nascimento, Fernando; Vinicius de Jesus Ribeiro, Matheus (Revista Gênero e Interdisciplinaridade, 2022)
This work sheds light on the importance of budget transparency at the national level through a study of the SIGA BRASIL portal. The objective is to understand how the operation of this electronic government helps to cover the expenses of public money resources and how, through it, it is possible to combat and monitor corruption practices in the public sector, in addition to seeking to answer questions related to access on the part of citizens to this system and if it has been bringing satisfactory results within the field of action. In order to achieve this objective, the studies of the following authors were used in the article as reference: Eugenio Raul Zaffaroni (1990), José Vitor Lemes Gomes (2016), Paulo Sérgio Sabino de Araújo (2008), Augustinho Paludo (2016) and Rodrigo Monteira da Silva (2016). The methodology used was descriptive of qualitative nature, where the data collection was done through the indirect document technique and the data analysis followed the document analysis technique. The main results obtained show that the SIGA BRASIL portal is more accessed by a group of people rated as “specialties in public budgeting” than by society in general. This system contributes to the fight against corruption as it issues reports on budget processes, enabling greater regulation and inspection by society and public authorities. Furthermore, this portal is proven to be an important transparency tool and fulfills its role effectively.